Innovation and communicative action: health management networks and technologies - Francisco Javier Uribe Rivera; Elizabeth Artmann
Abstract: This article discusses elements of a theory of innovation from the perspective of innovation networks and social construction of technology, based on Habermas' Theory of Communicative Action and authors from the Sociology of Innovation. Based on the theoretical framework of the communicative production of scientific facts, we focus on innovation management as a basic dimension that must meet some organizational and methodological requirements in order to power its results. We present and discuss instruments such as Situational Planning, Prospective Analysis, Strategic Portfolio Management, and Networks Management that can help deal with the challenge of innovation and exploration of the future. We conclude that network organizational formats centered on reflexivity of interdisciplinary groups and planning approaches that encourage innovation criteria in assessing the attractiveness of activities and that help anticipate forms of innovation through systematic prospective analysis can potentiate the process of generating innovation as a product of networks.